Accessing alpha-arylated nitriles via BF3 center dot OEt2 catalyzed cyanation of para-quinone methides using tert-butyl isocyanide as a cyanide source - Shirsath, Sachin R.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (Journal of Organic Chemistry, 2018)
BF3 center dot OEt2 catalyzed 1,6-conjugate addition of tertbutyl isocyanide to para-quinone methides and fuchsones for the synthesis of alpha-diaryl and alpha-triaryl nitriles has been reported. This protocol allows alpha-diaryl- and alpha-triaryl nitriles to be accessed in good to excellent yields and with a broad substrate scope, which could be further functionalized to give a versatile set of products. This is the first example wherein tert-butyl isocyanide has been used as a cyanide source for the 1,6-conjugate addition.

1,6-Conjugate addition initiated formal [4+2] annulation of p-quinone methides with sulfonyl allenols: a unique access to spiro[5.5]undeca-1,4-dien-3-one scaffolds - Ghotekar, Ganesh S.; Shirsath, Sachin R.; Shaikh, Aslam C.; Muthukrishnan, M. (Chemical Communications, 2020)
An expedient one-pot synthesis of carbocyclic spiro[5.5]undeca-1,4-dien-3-ones via 1,6-conjugate addition initiated formal [4+2] annulation sequences by employing p-quinone methides and sulfonyl allenols is presented. Furthermore, this synthetic protocol tolerates a wide variety of p-quinone methides and sulfonyl allenols and affords the corresponding structurally unique spiro[5.5]undeca-1,4-dien-3-ones in good yield under mild reaction conditions.

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Iron catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols with p-quinone methides: new access to gamma,gamma-diaryl ketones - Shirsath, Sachin R.; Chandgude, Sagar M.; Muthukrishnan, M. (Chemical Communications, 2021)
An iron(iii) catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols to p-quinone methides leading to gamma,gamma-diaryl ketones has been described. This catalytic protocol provides a novel and efficient method to access gamma,gamma-diaryl ketone derivatives in good to excellent yields with high functional group tolerance. Importantly, gamma,gamma-diaryl ketone can be further functionalized to give a versatile set of useful products.

Ultrasound assisted curcumin recovery from Curcuma aromatica: understanding the effect of different operating parameters - Shirsath, Sachin R.; Sable, Sunil S.; Gaikwad, Shashank G.; Gogate, Parag R. (Chemical Engineering and Processing-Process Intensification, 2021)
The present study deals with intensified extraction of curcumin from Curcuma aromatica by employing ultrasound-assisted extraction (UAE) approach also elucidating comparison with the conventional batch extraction to highlight the intensification benefits based on the usage of ultrasound. Understanding into the effect of operational parameters like type of solvent, extraction temperature, solid to solvent ratio and raw material size distribution as well as the equipment operating conditions as frequency and power on the extraction yield has been developed. Based on the results for extraction yield, the optimum conditions for UAE approach were 40 degrees C as temperature, 1:30 as solid to solvent ratio, 0.09 mm as the mean particle size, 240 W as ultrasonic power, 22 kHz as ultrasonic frequency and ethanol as the most suitable solvent. Under these optimum conditions, the highest extraction yield of 73.18% was achieved in 2 h whereas batch extraction for 14 h resulted in 52.31% yield clearly demonstrating the intensification due to ultrasound. Peleg's model was applied to explain the extraction kinetics of curcumin and the proposed model satisfactorily predicted the rates of extraction of cur cumin. Overall, UAE proved to be a better technique in terms of lesser time, lesser heating requirement and additional extraction yield.
Keywords: Cavitation; Curcuma aromatica; curcumin; Intensification; Kinetic modelling; Ultrasound assisted extraction

Metal-free aminocarbonylation of p-quinone methides with isocyanides: synthesis of sterically hindered alpha-arylated acetamides - Shirsath, Sachin R.; More, Devidas A.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2022)
The synthesis of sterically hindered alpha-arylated acetamides generally requires a multistep reaction sequence and is also difficult to access due to steric constraints. This protocol allows the synthesis of sterically hindered alpha-arylated acetamides in moderate to high yields via 1,6-addition of isocyanides to p-quinone methides in the presence of BF3 center dot OEt2. The present transformation features transition metal-free conditions, avoiding the use of toxic carbon monoxide, broad substrate scope, mild reaction conditions, and operational simplicity.
Keywords: Aminocarbonylation; Isocyanide; p-Quinone methide; Sterically Hindered alpha-Arylated Acetamides

Metal- and photocatalyst-free, visible-light-initiated C3 a-aminomethylation of quinoxalin-2(1H)-ones via electron donor-acceptor complexes - More, Devidas A.; Shirsath, Sachin R.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
We report a metal- and photocatalyst-free C3 a-aminomethylation of quinoxalin-2(1H)-ones with N-alkyl-N-methylanilines. The reaction proceeds through the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-ones and N-alkyl-N-methylanilines. The present method provides a mild and environmentally friendly protocol that exhibits good atom economy and excellent functional group tolerance to obtain a library of biologically significant C3 a-aminomethylated quinoxalin-2(1H)-ones in good yields.